Mapping and functional verification of leaf yellowing genes in watermelon during whole growth period - Zhu, Yingchun; Yuan, Gaopeng; Wang, Yifan; An, Guolin; Li, Weihua; Liu, Junpu; Sun, Dexi (Frontiers in Plant Science, 2022)
Increasing light energy utilization efficiency is an effective way to increase yield and improve quality of watermelon. Leaf is the main place for photosynthesis, and the color of leaf is directly related to the change of photosynthesis. In addition, leaf yellowing can be used as a marker trait to play an important role in watermelon hybrid breeding and improve seed breeding. It can not only be used to eliminate hybrids at seedling stage, but also be used to determine seed purity. In this study, transcriptome analysis was first carried out using the whole growth period leaf yellowing watermelon mutant w-yl and inbred line ZK, and identified 2,471 differentially expressed genes (DEGs) in the comparison group w-yl-vs-ZK. Among the top 20 terms of the gene ontology (GO) enrichment pathway, 17 terms were related to photosynthesis. KEGG pathway enrichment analysis showed that the most abundant pathway was photosynthesis—antenna proteins. The F2 population was constructed by conventional hybridization with the inbred line ZK. Genetic analysis showed that leaf yellowing of the mutant was controlled by a single recessive gene. The leaf yellowing gene of watermelon located between Ind14,179,011 and InD16,396,362 on chromosome 2 by using indel-specific PCR markers, with a region of 2.217 Mb. In the interval, it was found that five genes may have gene fragment deletion in w-yl, among which Cla97C02G036010, Cla97C02G036030, Cla97C02G036040, Cla97C02G036050 were the whole fragment loss, and Cla97C02G0360 was the C-terminal partial base loss. Gene function verification results showed that Cla97C02G036040, Cla97C02G036050 and Cla97C02G036060 may be the key factors leading to yellowing of w-yl leaves.